Analysis of the Effect of Stock Split Corporate Action on Stock Prices with Liquidity as an Intervening Variable - Muhammad Ilham Maulana; Indah Yuliana (University of Merdeka Malang, 2022)
This research aims to look at the effect of stock splits on stock prices with variable liquidity as intervening. The research sample consisted of 83 companies on the Indonesia Stock Exchange (IDX) that conducted a stock split corporate action in the period 2015-2020 with the requirement that the stock be active in stock trading (no suspension for a long time). The data taken on the study was 5 days before the stock split and 5 days after the stock split. Analysis tools used in the form of IBM SPSS 25 with methods of Path Analysis and Sobel Test. The results of the study found that: 1) stock split has a significant positive effect on stock prices and liquidity, 2)liquidity has a significant effect on stock prices, but is unable to mediate the effect of stock splits on stock prices.